The Effect of Comorbidities on the Prognosis of COVID-19 is More Than Thought: A Summary of Our Region - Bozoglan, Merve Yılmaz; Karlıdag, Gulden Eser (My University, 2022)
Objective: Nowadays community immunity is trying to be achieved through vaccination. If the threshold value can be exceeded, COVID-19 may also be one of the seasonal infections with annual epidemics like influenza. The current study intends to understand how the most common underlying comorbidities affect the intensive care unit (ICU) and mechanical ventilation (MV) requirements and mortality of COVID-19. Materials and Methods: Main demographic data, laboratory, and radiological findings were obtained retrospectively from medical records of 152 patients diagnosed with COVID-19. Comorbidities were ensured from the prescription information system. Effect of all data on ICU and MV requirements and mortality were analyzed with Student's t-test, Mann-Whitney-U, or Chi- square tests. Length of hospital stay was evaluated according to univariate analyzes. Results: Out of 152 patients, 72 were men. The median age was 56.5 years. The median length of hospital stay was 7 days. The case fatality rate was 5.9%. Elderly ages, clinical symptoms during admission, and laboratory values increased the risk of ICU, MV and mortality significantly (p<0.05). At least one or more comorbidities were present in nearly half of the patients. The most prevalent comorbidities were hypertension, diabetes, and cardiovascular diseases, respectively. Especially diabetes was significantly associated with poor prognosis (p<0.05). Conclusion: COVID-19 patients with any comorbidity yielded poorer clinical outcomes. Awareness of comorbidities, trying to cure them, and striving for maintaining a high personal health status seems to prevent the bad prognosis of the COVID-19.
Keywords: COVID-19; SARS-COV-2; mortality; diabetes; intensive care